THE EFFECT OF HYPERTENSION EXERCISE AND FOOT MASSAGE THERAPY ON REDUCING BLOOD PRESSURE IN HYPERTENSION PATIENTS IN MEKARJAYA VILLAGE, PURWASARI DISTRICT, KARAWANG REGENCY - Sarini; Desty Lismayanti; Yanti Rosmayanti; Sumitro, Sumitro; Okti Rahayu Asih; Nining Sugihartati; Yazin Azhari (Bajang Institute, 2024)
Hypertension is defined as a condition where a person experiences an increase in blood pressure above normal which can result in morbidity and mortality. Hypertension, which means very high blood pressure in the blood vessels, which carry blood from the heart which pumps blood to all tissues and organs of the body. Mekarjaya Village has cases of hypertension with the number of cases being 58% of the PTM census of 3 hamlets in the working area of ​​the Purwasari Health Center. The aim of this study was to determine the effect of hypertension exercise therapy and foot massage therapy on blood pressure in hypertensive patients. The research was conducted on 48 hypertensive patients in Mekarjaya village, Purwasari district. The treatment was carried out by carrying out hypertension exercise activities in Krajan Hamlet for 24 people as the intervention group and 24 people as the control group. For the intervention, there were 24 people in the foot massage therapy intervention group and 24 people in the control group. This research method is quantitative, a pretest-posttest quasi-experimental design with control group design, the sample used was 72 elderly people with hypertension. The results of the study stated that there was a significant effect on the hypertension exercise group and the foot massage therapy group before and after the intervention with a p-value (0.000); (0.001). Conclusion: Hypertension exercise and foot massage interventions are both effective interventions to help reduce blood pressure in hypertensive patients